Systematic review of studies generating individual participant data on the efficacy of drugs for treating soil-transmitted helminthiases and the case for data-sharing. - Julia B Halder; Joanne Benton; Amélie M Julé; Phillipe J Guérin; Piero L Olliaro; María-Gloria Basáñez; Martin Walker (PLoS Neglected Tropical Diseases, 2017)
Background Preventive chemotherapy and transmission control (PCT) by mass drug administration is the cornerstone of the World Health Organization (WHO)'s policy to control soil-transmitted helminthiases (STHs) caused by Ascaris lumbricoides (roundworm), Trichuris trichiura (whipworm) and hookworm species (Necator americanus and Ancylostama duodenale) which affect over 1 billion people globally. Despite consensus that drug efficacies should be monitored for signs of decline that could jeopardise the effectiveness of PCT, systematic monitoring and evaluation is seldom implemented. Drug trials mostly report aggregate efficacies in groups of participants, but heterogeneities in design complicate classical meta-analyses of these data. Individual participant data (IPD) permit more detailed analysis of drug efficacies, offering increased sensitivity to identify atypical responses potentially caused by emerging drug resistance. Methodology We performed a systematic literature review to identify studies concluding after 2000 that collected IPD suitable for estimating drug efficacy against STH. We included studies that administered a variety of anthelmintics with follow ups less than 60 days after treatment. We estimated the number of IPD and extracted cohort- and study-level meta-data. Principal findings We estimate that there exist individual data on approximately 35,000 participants from 129 studies conducted in 39 countries, including 34 out of 103 countries where PCT is recommended. We find significant heterogeneity in diagnostic methods, times of outcome assessment, and the reported measure of efficacy. We also quantify cohorts comprising pre-school age children, pregnant women, and co-infected participants, including with HIV. Conclusions We argue that establishing a global IPD repository would improve the capacity to monitor and evaluate the efficacy of anthelmintic drugs, respond to changes and safeguard the ongoing effectiveness of PCT. Establishing a fair, transparent data governance policy will be key for the engagement of the global STH community.